KEY FACTORS CONTRIBUTING TO THE SUCCESS OF SME PARTNERSHIP PROGRAMS: INSIGHTS FROM PT PERKEBUNAN NUSANTARA III - Junaidi, Junaidi; Purjianto, Purjianto; Febrianto, Eka Bobby; Maisarah, Maisarah (Jurnal Bisnis Tani, 2024)
This research aims to identify the key factors influencing the success or failure of partnership programs for SMEs, specifically those fostered by PT. Perkebunan Nusantara III. The study fills gaps in existing literature and offers practical recommendations for enhancing partnership program design and implementation. Data were gathered from 243 SME business actors using a structured questionnaire, and multiple linear regression analysis was employed to evaluate the relationships between various independent variables and the success of the programs. The findings indicate that experience, knowledge, social networks, and business performance positively affect program success, while communication barriers and high transaction costs hinder success. However, factors like funding amount and communication behavior were found to be insignificant in this context. Based on these results, the study recommends investing in partner training to improve experience and knowledge, developing effective communication strategies, reducing transaction costs, and leveraging social networks. These recommendations aim to enhance the effectiveness of partnership programs, supporting the growth of SMEs and contributing to policy and practice in both Indonesia and globally.